SYSTEM AND MARKETING STRATEGY ANALYSIS OF TOFU INDUSTRY IN MEURAH MULIA DISTRICT - Riskiani; Iskandar; Khalish Khairina (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
This study discusses System and Marketing Strategy Analysis in the Tofu Industry (Case Study on the Samani Tofu Industry in Meurah Mulia District). Samani Tofu Industry has a big potential in tofu industry, but still restricted by marketing system, promotion, capital, and also higher price material. Thus, this study aim to analyze its system and marketing strategy. This research is a field research with a qualitative approach. This study uses data collection techniques, namely interviews, observation and documentation. Based on the results of the study, it was found that the marketing system of the tofu in the Samani tofu industry in Meurah Mulia District includes quality raw materials, competent employees, a clean and strategic place and cooperation with local community transportation. Mean while, marketing system of the tofu in the Samani tofu industry in Meurah Mulia by producing high quality products, offer a lower price, affordable among the community. distribution strategy applied to Samani's tofu business is by directing it into the hands of consumers and also through intermediaries, namely retailers, direct approach with community and word of mouth.